The Relationship between Cytokines and Toxoplasma Infection in Heart Disease Patients - A. Al-Aboody, Bassad; S. Abdulhussein, Haider; H. Mohammed, Ahmed (University of Thi-Qar Journal of Science, 2019)
Toxoplasmosis is the general term for infection and disease in man and animal caused by a parasite called Toxoplasma gondii, this disease is prevalent among different categories of people, Heart disease are one of them. Because of the dormancy status of T. gondii, there is ambiguity and variation in the immunity of patients. This study aimed to investigate the immune status of heart disease patients infected with toxoplasmosis. Two hundred and fifty samples of both heart disease patients and controls had been tested by ELISA technique to detect anti-Toxoplasma Abs (IgG and IgM). The positive samples with toxoplasmosis were tested to detect the level of interleukins (IL-10, IL-12 and IL-17). The result of this study revealed the prevalence of toxoplasmosis among heart disease patient in about (43.33% IgG and 0.66% IgM). The results of interleukins appeared high level of IL-12 (82.85 pg./ml) in heart disease patients infected with toxoplasmosis when compared with control (60.97 pg./ml) with significant difference between them at p≤0.05, while there was no significant difference in IL-10 between patients and controls. The results also showed decreased level of IL-17 in patients with heart disease. The increased level of IL-12 in patient with heart disease infected with toxoplasmosis indicate to the activity of cell mediated immunity in those patients and may be lead to provoke an inflammatory status in the heart valves and muscle then worse heart disease to be sever and need complicated treatments